An innovative synthetic support for immunocytochemical assessment of cytologically indeterminate (Bethesda III) thyroid nodules - Taccogna, Silvia; Papini, Enrico; Novizio, Roberto; D’Angelo, Martina; Turrini, Luca; Persichetti, Agnese; Pontecorvi, Alfredo; Guglielmi, Rinaldo (Frontiers in Endocrinology, 2022)
Background. Fine needle aspiration (FNA) is the procedure of choice in the evaluation of thyroid nodules. Nodules with indeterminate cytological categories, Bethesda III and IV, pose challenges in clinical practice and are frequently submitted to diagnostic surgery. CytoFoam Core (CFCS) uses an absorbent foam device inserted into the needle hub to collect the cytological sample aspirated during FNA. Specimen is formalin-fixed and paraffin-embedded. Aim of the study. Assessing diagnostic efficacy of CFCS, compared to traditional cytology, in re-evaluating thyroid nodules classified as Bethesda III, using post-surgical histology as reference standard. Method. Retrospective study on 89 patients with a first indeterminate cytological report who were referred to the Department of Endocrinology of Regina Apostolorum Hospital (Albano L. Rome, Italy) for a second FNA. FNA was performed after at least one month under ultrasound guidance with a 23G needle according to the established procedure. During the second procedure, both traditional cytological (TC) smears and a single-pass CFCS specimen were obtained for each patient. On CFCS samples immunocytochemical staining for Galectin-3, HBME-1, and CK-19 was also performed. 51 patients eventually underwent surgery, and their histological diagnoses were compared to the TC and CFCS reports. Four parameters were evaluated: inadequacy rate, rate of persistent indeterminate (Bethesda III and IV) reports, rate of malignancy in persistently indeterminate nodules, and rate of cancer in lesions cytologically classified as malignant. Results. Non-diagnostic samples were 6 (11.8%) in TC vs 3 (5.9%) in CFCS (p=0.4). Persistent indeterminate samples were 31 (60.8%) in TC vs 19 (37.2%) in CFCS (p=0.01). Rate of malignancy in persistently indeterminate nodules was 8/19 (42.1%) in CFCS vs 9/31 (29%) in TC group (p=0.3). Nine/51 (17.6%) samples were classified as benign by TC vs 21/51 (41.2%) samples by CFCS (p<0.01). All nodules resulted benign at post-surgical evaluation. Five/51 (9.8%) samples were classified as suspicious for malignancy/malignant in TC group against 8/51 (15.7%) samples in CFCS (p=0.5). Post-surgical evaluation confirmed malignancy in all these cases. Conclusion. CFCS demonstrated greater diagnostic accuracy than TC in repeat FNA assessment of cytologically indeterminate nodules. CFCS increased the conclusive diagnosis rate and decreased the number of cytologically indeterminate cases.